Trace elements and oxygen isotopes of gem spinels in marble from the Luc Yen - An Phu areas, Yen Bai province, North Vietnam - Long, Pham Van; Giuliani, Gaston; Fallick, Anthony E.; Boyce, Andrian J.; Pardieu, Vincent (Vietnam Journal of Earth Sciences, 2018)
Trace elements investigated by electron microprobe analysis (EMPA) have been combined with oxygen isotopic composition of pink, red and other colored spinels (blue, purple, brown, orange, lavender) hosted by marbles and found in placers from Luc Yen and An Phu deposits, Yen Bai province, North Vietnam. The deposits are those from Nuoc Ngap, Cong Troi, Bai Son and different placers from the An Phu area. Trace elements such as Fe-Zn-Cr-V in red and pink gem spinels permit to separate those from Cong Troi and those from the others deposits of the An Phu area. Spinels from Cong Troi have low to extremely low Zn (< 500 ppm) and high Fe contents (3,000 to 16,000 ppm) while those from An Phu area are Zn-rich (up to 11,000 ppm). Iron is the dominant element for the other colored spinels whereas Zn, Cr and V contents are extremely variable. The Bai Son blue spinel is Fe-rich (5,000 to 7,200 ppm) with some V (950 to 1,830 ppm), Cr (270 to 480 ppm), Co (240 to 400 ppm) and Ni (550 to 950 ppm). The O-isotope composition of the whole spinels ranges between 12.1 and 24.2‰ (n = 25). Within each deposit, the range of δ18O values for red, pink and colored spinels is usually similar. However, the red and pink spinels from An Phu present two distinct sets of δ18O values, respectively between 13.2 to 17.0‰ (n = 7) and 22.5< δ18O < 24.2 (n = 5). Those from Cong Troi are from 14.8 to 17.7‰ (n = 3) and their range overlaps that of An Phu. The use of O-isotopes is not useful for distinguishing between the deposits, but the low to extremely low Zn content of the Cong Trois spinels is a discriminant. The variation of δ18O values (12.1 <δ18O < 24.2‰) of the whole spinels indicates that the oxygen isotopic compositions of the metamorphic fluids were probably buffered by the local δ18O values of the impure host marbles. References Chauviré B., Rondeau B., Fritsch E., Ressigeac Ph., Devidal J.-L., 2015. Blue spinel from the Luc Yen district of Vietnam. Gems & Gemology, 51, 2-17. D’Ippolito V., Andreozzi G.B., Hålenius H., Skogby H., Hametner K., Günther D., 2015. Colour mechanisms in spinel: cobalt and iron interplay for the blue colour. Physics and Chemistry of Minerals, 42, 431-439. Garnier V., 2003. Les gisements de rubis associés aux marbres de l’Asie Centrale et du Sud-est: genèse et caractérisation isotopique. PhD thesis INPL, Nancy, France, 373p. Garnier, V., Ohnenstetter, D., Giuliani, G., Maluski, H., Deloule, E., Phan Trong Trinh, Pham Van Long, Hoang Quang Vinh, 2005. Age and significance of ruby-bearing marbles from the Red River shear zone, northern Vietnam. The Canadian Mineralogist, 43, 1315-1329. Garnier V., Giuliani G., Ohnenstetter D., Fallick A.E., Dubessy J., Banks D., Hoang Quang Vinh, Lhomme Th., Maluski H., Pêcher A., Bakhsh K.A., Pham Van Long, Phan Trong Trinh, Schwarz D., 2008. Marble-hosted ruby deposits from central and Southeast Asia: towards a new genetic model. Ore Geology Reviews, 34, 169-191. Giuliani G., Fallick A.E., Garnier V., France-Lanord Ch., Ohnenstetter D., Schwarz D., 2005. Oxygen isotope composition as a tracer for the origins of rubies and sapphires. Geology, 33(4), 249-252. Giuliani G., Fallick A.E., Boyce A.J., Pardieu V., Pham Van Long, 2017. Pink and red spinels in marble: trace elements, oxygen isotopes, and sources. The Canadian Mineralogist, 55, 743-761. Hauzenberger C.A., Häeger T., Baumgartner L.P., Hofmeister W., 2001. High-grade metamorphism and stable isotope geochemistry of N-Vietnamese gem-bearing rocks. In: Proceedings of the Workshop on gems and minerals of Vietnam, Hanoi, 124-138. Hauzenberger C.A., Bagola C., Häeger T., Muellen C., Nguyen Ngoc Khoi, Le Thi Thu Huong, 2014. Mineralogy and petrology of the An Phu marble hosted spinel and corundum deposit, Luc Yen, N-Vietnam. In Proceedings of the 4th International Gem and Jewelry Conference, Chiang Mai, Thailand, 76-78. Kleišmantas A., Daukšyte A., 2016. The influence of Vietnam and Sri Lanka spinel mineral chemical elements on colour. Chemija, 27, 45-51. Kretz R., 1983. Symbols for rock-forming minerals. American Mineralogist, 68, 277-279. Le Thi Thu Huong, Häeger T., Hofmeister W., Hauzenberger C., Schwarz D., Pham Van Long, Wehmeister U., Nguyen Ngoc Khoi, Nguy Tuyet Nhung, 2012. Gemstones from Vietnam: An update. Gems & Gemology, 48, 158-176. Malsy A., Klemm L., 2010. Distinction of gem spinels from the Himalayan mountain belt. Chimia, 64(10), 741-746. Malsy A., Karampelas S., Schwarz D., Klemm L., Armbruster T., Tuan Do Anh, 2012. Orangey-red to orangey-pink gem spinels from a new deposit at Lang Chap (Tan Huong - Truc Lau), Vietnam. The Journal of Gemmology, 33, 19-27. Pham Van Long, Hoang Quang Vinh, Garnier V., Giuliani G., Ohnenstetter D., Lhomme,T., Schwarz D., Fallick A.E., Dubessy J., Phan Trong Trinh, 2004. Gem corundum deposits in Vietnam. Journal of Gemmology, 29, 129-147. Pham Van Long, Pardieu V., Giuliani G., Nguy Tuyet Nhung, Pham Thi Thanh Hien, Pham Duc Anh, Nguyen Ngoc Khoi, Hoang Quang Vinh, 2014. Gemmological characteristics of spinel from Luc Yen, Yen Bai. Journal of Geology, 340, 29-36. Pham Van Long, Pardieu V., Giuliani G., 2014. Update on gemstone mining in Luc Yen, Vietnam. Gems & Gemology, 49, 233-245. Pouchou J.L., Pichoir F., 1991. Quantitative analysis of homogeneous or stratified microvolumes applying "PAP" In Electron Probe Quantification (K.F.J. Heinrich & D.E. Newbury eds.). Plenum Press, New York, USA, 31-75. Valley J.W., 1986. Stable isotope geochemistry of metamorphic rocks. Reviews in Mineralogy, 16, 445-481. Yui T.F., Khin Zaw, Wu C.-M., 2008. A preliminary stable isotope study on Mogok ruby, Myanmar. Ore Geology Reviews, 34, 182-199.